Effectiveness of shared decision-making intervention in patients with lumbar degenerative diseases: A randomized controlled trial. Issue 10 (October 2021) - Chen, Chia-Hsien; Kang, Yi-No; Chiu, Po-Yao; Huang, Yi-Jing; Elwyn, Glyn; Wu, Meng-Huang; Kang, Jiunn-Horng; Hou, Wen-Hsuan; Kuo, Ken N
Highlights: Shared decision-making is critical for patients with lumbar degenerative diseases. A randomized controlled trial investigated decision coaching and decision aids. Shared decision-making intervention improves decisional conflict and self-efficacy. Abstract: Objective: To evaluate the efficacy of shared decision-making (SDM) intervention among patients with lumbar degenerative diseases (LDDs) in terms of decision self-efficacy, control preferences, SDM process, decision satisfaction, and conflict. Methods: A total of 130 outpatients with LDDs recruited from orthopedic or rehabilitation clinics were randomly assigned to the SDM intervention (n = 67) or comparison (n = 63) groups. Patients in the intervention group received decision aids (DAs) with decision coaching and those in controlled group received standard educational materials from a health educator. The primary outcome was decision self-efficacy, and secondary outcomes were control preference, SDM process, conflict, and satisfaction. Results: The SDM intervention significantly improved decision self-efficacy (mean difference [MD] = 7.1, 95% confidence interval [CI]: 1.7–12.5, partial η 2 = 0.05) and reduced conflict (MD = −7.0, 95% CI: −12.2 to −1.9, partial η 2 = 0.06), especially in patients without family involvement, compared with the health education group. However, no significant between-group differences were observed in other outcomes. Conclusion: SDM intervention improved SDM self-efficacy and reduced conflict in patients with LDDs. Practice Implications: Clinicians can integrate DAs and decision coaching in SDM conversations. SDM intervention seems to engage patients in decision-making, especially those without family involvement.